2012
DOI: 10.1093/cercor/bhs092
|View full text |Cite
|
Sign up to set email alerts
|

Chronic In Vivo Imaging Shows No Evidence of Dendritic Plasticity or Functional Remapping in the Contralesional Cortex after Stroke

Abstract: Most stroke survivors exhibit a partial recovery from their deficits. This presumably occurs because of remapping of lost capabilities to functionally related brain areas. Functional brain imaging studies suggest that remapping in the contralateral uninjured cortex might represent a transient stage of compensatory plasticity. Some postmortem studies have also shown that cortical lesions, including stroke, can trigger dendritic plasticity in the contralateral hemisphere, but the data are controversial. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…Surviving neurons in the peri-infarct cortex undergo active structural and functional remodeling, which is associated with a remapping of lost function (Brown et al, 2009;Mostany et al, 2010). Longitudinal two-photon imaging approaches have demonstrated compensatory dendritic spine production in recovering circuits in the weeks after stroke that was specific to the peri-infract zone (Brown et al, 2009;Johnston et al, 2013;Mostany et al, 2010). Although turnover was specific to the peri-infarct zone, it is possible that these studies were not sufficiently sensitive to resolve structural rearrangements involving a relatively small fraction of the total inputs to a distant area in the background of many unchanged connections.…”
Section: Local and Remote Structural-functional Changes To Connectomementioning
confidence: 99%
See 1 more Smart Citation
“…Surviving neurons in the peri-infarct cortex undergo active structural and functional remodeling, which is associated with a remapping of lost function (Brown et al, 2009;Mostany et al, 2010). Longitudinal two-photon imaging approaches have demonstrated compensatory dendritic spine production in recovering circuits in the weeks after stroke that was specific to the peri-infract zone (Brown et al, 2009;Johnston et al, 2013;Mostany et al, 2010). Although turnover was specific to the peri-infarct zone, it is possible that these studies were not sufficiently sensitive to resolve structural rearrangements involving a relatively small fraction of the total inputs to a distant area in the background of many unchanged connections.…”
Section: Local and Remote Structural-functional Changes To Connectomementioning
confidence: 99%
“…After effective rehabilitation, the human premotor cortex develops increased functional connectivity with ipsilesional M1 , thus potentially serving as an effective target for brain stimulation-based therapies (Dancause, 2006;Plow et al, 2014). The presence of structural reorganization in the contralesional hemisphere has been less clear, as some animal work suggests homotopic regions ( Figure 2B) to the infarct can support recovery (Biernaskie et al, 2004) and undergo structural remodeling (Takatsuru et al, 2009), while other mouse longitudinal imaging work indicates no poststroke structural reorganization (Johnston et al, 2013). Conceivably, these differences may be related to the subsets of regions assessed, or the possibility that apparent contralateral cortex remapping may involve non-structure-based rearrangements in function.…”
Section: Local and Remote Structural-functional Changes To Connectomementioning
confidence: 99%
“…Given our results, Fmr1 KO mice would be expected to show impairments in behavioral tasks that assess tactile perception and perceptual decision making. Indeed, these mice have demonstrated impaired texture discrimination during novel object recognition (Orefice et al, 2016), as well as reduced whisker sampling (Juczewski et al, 2016) and impaired learning (Arnett et al, 2014) in the gap-crossing assay.…”
Section: Discussionmentioning
confidence: 99%
“…Following cranial window surgery, optical intrinsic signal (OIS) imaging was used to map the barrel cortex at P12-P14 (for P14 -P16 imaging) or at least 1 d before imaging (for adults). As described previously (Johnston et al, 2013), the contralateral whisker bundle was gently attached using bone wax to a glass needle coupled to a piezoactuator (Physik Instrumente). Each stimulation trial consisted of a 100 Hz sawtooth stim- ulation lasting 1.5 s. The response signal divided by the averaged baseline signal, summed for all trials, was thresholded at a fraction (65%) of maximum response to delineate the cortical representation of stimulated whiskers (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Data from our laboratory and that of others have shown that increasing the excitability of the ipsilesional motor cortex (iM1) after stroke is beneficial for recovery [5,23,26,27]. However, it is less clear whether activation of other areas such as the contralesional cortex is beneficial or maladaptive, or not involved [28]. Furthermore, most cortical remapping studies have relied on peripheral stimulations such as limb movement, which is limited to sensory and/or motor cortex activation, and have neglected subcortical and other remotely connected brain regions.…”
Section: Functional Recovery After Strokementioning
confidence: 92%